(untitled) (Boston, Mass, 1998)
This text can be used in International Insurance courses, in topical seminars, and as a supplement to Principles of Insurance/Risk Management or Risk Management texts where the instructor wants a more global emphasis. It will also draw interest in the professional market, with a number of practitioners as contributing authors to the text.
Keywords: Insurance companies,Risk (Insurance),Rủi ro (bảo hiểm),Công ty bảo hiểm; Management,Quản lý